Neoadjuvant compared to adjuvant chemotherapy combined with trastuzumab in patients with HER2-positive breast cancer: a register-based cohort study - S. Hosseini-Mellner; Å. Wickberg; E. Olsson; A. Karakatsanis; A. Valachis (ESMO Real World Data and Digital Oncology)
Background: The aim of the study was to compare trastuzumab-based neoadjuvant therapy (NAT) with adjuvant therapy (AT) in a register-based cohort of Swedish patients with primary operable human epidermal growth factor receptor 2 (HER2)-positive breast cancer. Patients and methods: The Swedish nationwide research database BCBaSe 3.0 was used to identify eligible patients with primary operable HER2-positive breast cancer treated with either NAT or AT between 2008 and 2019. To mitigate confounding by indication bias, propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) were applied. Results: In total, 7258 patients with primary operable HER2-positive breast cancer were identified; 1789 (24.6%) received NAT and 5469 (75.4%), AT. After 1 : 1 PSM, 1258 patients in each therapeutic strategy were available for comparisons. No statistically significant differences between NAT and AT were observed [hazard ratio (HR) for distant disease-free survival 0.97, 95% confidence (CI) 0.72-1.30; HR for breast cancer-specific survival (BCSS) 0.69, 95% CI 0.45-1.07; HR for overall (OS) 0.72, 95% CI 0.50-1.05]. In subgroup analysis, NAT resulted in better BCSS (HR 0.44, 95% CI 0.22-0.89) and OS (HR 0.49, 95% CI 0.29-0.90) in patients with clinical node positivity (cN+) at diagnosis. Conclusion: The study shows an equivalence of NAT and AT in terms of prognosis for patients with operable HER2-positive disease whereas a potential benefit of NAT in patients with cN+ is implied. Considering the emerging treatment strategies in the neoadjuvant setting for HER2-positive breast cancer that are not reflected in the study cohort, NAT should be considered as the strategy with a higher possibility of improving long-term prognosis for patients with HER2-positive disease.